Minutiae Based Partial Fingerprint Registration and Matching Method - Varol, Asaf; Ahmed, Naveed (Ieee, 2018)
Everyone in this world has a unique set of fingerprints and these fingerprints do not change throughout one's life, and is not questionable. The question is whether investigators can accurately link the collected fingerprints to the offender. Our proposed method can be used to match partial fingerprints with collection of fingerprints of all known criminals and suspects. In this method system completely relies on localized features (minutiae) for registration and matching process. Due to localized in nature minutiae are invariant to translation, rotation and displacement. Errors in alignment lead to errors in matching process.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: partial fingerprints; ten-prints; minutiae; bifitrcation points; termination points; segmentation; normalization; binarization; thinning; crossing number